Teachers' perceptions on collaborative activity in ESL writing class - Yong, Mei Fung; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2008)
This study focused on teachers' perceptions of collaborative writing and how this activity was enacted in the classroom. Data were collected from a questionnaire and a semi-structured interview with 16 instructors who taught an academic writing course at Universiti Putra Malaysia. The findings revealed that collaborative activity is beneficial because it could enhance the development of cognitive and social skills and boost students' confidence in writing. On the contrary, the disadvantages of collaborative work are attributed by passive and uncooperative members as well as time factor. The findings also showed that the ways collaborative activities were enacted differed among the instructors. In addition, the choice of assigning groups and roles to students was also found to be varied. The insights from the teachers' perceptions are useful in improving the pedagogical applications of collaborative writing.